Pelatihan Dan Pendalaman Ilmu Organisasi Di Ikatan Santri, Siswa, Mahasiswa, Alumni Dan 'Ulama Nusa Tenggara Barat Orsat Jombang - Sunardi, Sunardi; Senang, Senang; Munfarida, Isah; Wijono, Hani Adi; Kartiko, Ari (An Naf'ah: Jurnal Pengabdian Masyarakat, 2024)
The Association of Santri Students and Scholars of West Nusa Tenggara (ISMA'U NTB) Jombang, whose existence is a forum for unity of all Students from West Nusa Tenggara Province residing in Jombang and also to accommodate their aspirations for the advancement of West Nusa Tenggara Province in particular and Indonesia in general. The purpose of this community service is to explain the understanding of relevant things in the organization, understanding the meaning and measurement of organizational effectiveness, and understanding ideal organizational charts. The strategy used is a training/workshop system and interactive discussions. As for the results of community service carried out at Isma'u West Nusa Tenggara Orsat Islamic Boarding School Al-Urwatul Wutsqo Jombang, it can increase knowledge and understanding of the importance in the organization to design and create and develop an ideal organizational structure, increase the skills of all administrators and members of the organization in performing according to their respective jobs, the awareness of all members of the organization on the importance of increasing understanding, deepening of the organization.